“Aplicación móvil de realidad aumentada para enseñar inglés a los niños del ciclo inicial en el centro de desarrollo infantil Kindergarten, en la ciudad de Latacunga” - Pionce Tasipanta, Miguel Joao (2021)
This degree work is focused on the development and production of the KinderAR application, an educational application designed for children from 3 to 5 years old, which allows teaching English vocabulary using augmented reality as a didactic support. Augmented reality is a virtual tool that has great acceptance by users around the world, its contribution has been very successful in various fields such as education, as it allows interacting with digital objects within the real environment, enriching new visual experiences improving the quality of education with the information presented. For which this project had place of execution in the child development center Kindergarten, located in the city of Latacunga, province of Cotopaxi. Through interviews with the director of the child development center and the kindergarten teacher, it was determined that one of the main factors is the absence of the use of technological tools by the kindergartens, which are limited to the use of traditional methods to teach English language that affect the performance of children in the classroom. Therefore, in this project a mobile application was developed to facilitate the learning of English vocabulary both inside and outside the classroom. To achieve a functional application, it was necessary the implementation of an agile development methodology, the Mobile-D methodology, is a methodology that stands out for its ease to make changes and is designed for small groups of developers, streamlining the development of the different processes or tasks proposed in the project. By managing this development methodology helped to structure the entire project in an organized way. In addition, to build an interactive application we used mobile application development tools such as Unity along with the Vuforia SDK to capture the real environment and 3D models designed in Blender, multimedia image files created in GIMP. And the pronunciation of the English vocabulary elaborated in Kukarela, with the resources obtained we were able to develop an application capable of teaching words of different topics of the English vocabulary without the need to have access to the internet, benefiting children and teachers of the institution to integrate with new technologies for the development of education.